Cage culture with tilapia induces alteration in the diet of natural fish populations: the case of Auchenipterus osteomystax - Strictar-Pereira,L. (2010)
Fish rearing in cages installed in reservoirs has developed rapidly in Brazil over the last decade. However, this type of aquaculture induces some changes in the environment because of the high quantity of nutrients released into the surroundings. This study evaluated trophic changes resulting from these nutrient inputs into the diet, feeding activity and nutritional condition of Auchenipterus osteomystax, an insectivore that alternatively feeds on zooplankton. Fish were sampled with gillnets in two tilapia (Oreochromis niloticus) experimental caging aquaculture areas of the Rosana reservoir (Paranapanema River), at different distances from the cages. Samplings were carried out for 90 days (before the cages were installed and 30 and 60 days after installation). Diet analysis was based on 250 stomach contents evaluated with occurrence and volumetric methods, combined into a Feeding Index. The spatial and temporal variations in feeding activity were inferred by the stomach repletion index (stomach weight). The relative condition factor was used to evaluate the individual nutritional condition of the sampled fish. Insects and zooplankton accounted for more than 85% of the diet in any sample. Insects predominated before caging culture started and at the end of the sampling period, whereas zooplankton predominated 30 days after caging began. The repletion index increased at 30 days after caging in both areas when the condition factor was the lowest, with some recovery at the end of this period. The input of nutrients near caging areas caused a short elevation in zooplankton availability, which promoted changes in the diet of this opportunist species, increasing its feeding activity. However, these changes appeared to be unsustainable due to the poor nutritional condition of the individuals.